The gender gap in STEM: (Female) teenagers’ ICT skills and subsequent career paths - Friederike Hertweck; Judith Lehner (PLoS ONE, 2025)
Skills shortage in the fields of Sciences, Technology, Engineering, and Mathematics (STEM) poses a significant challenge for industries globally. To overcome shortage of STEM talent, the selection into STEM fields must be fully understood. We contribute to existing research on the selection of STEM careers by analysing the interplay between teenagers’ proficiency in Information and Communication Technology (ICT) and their career preferences in the STEM domain. Based on representative data for German teenagers, our study shows that female teenagers are less likely to choose a career in STEM unless they have strong ICT skills in secondary school. The relationship does not hold for male students. An increase in girls’ ICT skills by 10 percentage points in ninth grade is associated with an increase in the probability to choose a STEM career by 2.95 percentage points. Our findings can be explained with evidence that teenagers sort into occupations they believe to be good at and that female teenagers rather underestimate their true potential. Using different empirical approaches, we also show that ICT skills act as a moderator and not as a mediator in the gender-specific choice of training upon graduating from secondary school. By addressing the interplay between gender, ICT skills, and educational choices, the present study uncovers an additional lever of how to mitigate skills shortage in STEM.